CREATIVE THINKING AND ITS RELATIONSHIP TO COGNITIVE AND SKILL ACHIEVEMENT IN HANDBALL AMONG SECOND-YEAR STUDENTS - Lecturer. Yasser Reda Qanbar; Lecturer. Imad Abbas Hussein; Lecturer. Mahmoud Abbas Hussein (American Journals, 2023)
Researchers in the field of education, physical education and sports sciences have been interested in the subject of creative thinking and its applications as it is one of the important mental activities that influence the athlete’s personality and determine his behavior in the environment in which he lives, with the belief that there is a clear impact of individual differences between individuals in the nature of the mental abilities that distinguish them from each other. The other. Since the handball event is one of the important sporting events that attracts a lot of attention among students in colleges of physical education, and given the student’s need to understand the nature of skill and cognitive performance through the basic vocabulary of the handball subject, the importance of the research lies in how to achieve the best learning process from both theoretical and practical perspectives. Therefore, measuring creative thinking and knowing the extent of its relationship to cognitive and skill achievement. The problem of the research lies in the lack of a test for cognitive achievement in the subject of handball. The need arose to work on building a test for this purpose through the use of precise scientific methods in order to address the basic research problem, And skills in handball. The aim of the study is to identify the relationship between creative thinking and cognitive and skill achievement in handball among second-year students at the College of Physical Education and Sports Sciences - Kirkuk University.The hypothesis
Keywords: Creative thinking, cognitive and skill achievement, handball.